Text and image in dialogue :|revisiting Iron age neo-Hittite stelae - Şen, Sait Kutay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Monumental Hieroglyphic Luwian inscriptions proliferated in the southeastern Anatolia and northern Syria in the Iron Age, after their emergence at the end of the Bronze Age in Hittite Anatolia. These inscriptions were carved in a pictographic writing system called the Anatolian hieroglyphs. This thesis investigates the connections between textual and visual aspects of Anatolian hieroglyphic writing by scrutinizing three stelae, all produced around the 9th century B.C., presenting an inscription together with an image of the Storm-god Tarhunzas. Recently, when the writing system was deciphered and the language was identified, the focus of the scientific endeavors was on the linguistic and morphological aspects of the inscriptions. Because writing is primarily a visual mode of expression, however, the imageness of the inscription is as significant as its textual content in understanding a monument as comprehensively as possible. Therefore, this study discusses the textual content of the inscriptions, the visual and semantic organization of the inscriptions on monuments; execution, appearance and placement of individual pictograms; and the connections between texts, signs and the Storm-god figures by applying a wholistic and comparative approach. These are not individual and isolated aspects of Anatolian hieroglyphic monumental inscriptions. They rather affect each other, take form with reference to each other and intersect to form a single monument that exist in a semantic integrity. Thus, as this thesis argues, while textual and visual signification take place codependently at the same time through the Anatolian hieroglyphs, the monument becomes the setting of a text-image cross-over.
Keywords: Hittites.; Hieroglyphics.; Iron Age -- Turkey; Iron age -- Syria.